The Role of Trust and Zakat Literacy on Muzakki's Interest in Paying Zakat with Attitude as a Mediating Variable in the Malang Raya OPZ - Amiruddin Amiruddin; Siswanto Siswanto; Umi Julaihah (al-Afkar, Journal For Islamic Studies, 2026)
Indonesia has a vast zakat potential, thanks to its world's largest Muslim population. However, zakat collection remains low, including in the Greater Malang area. Low levels of literacy and trust in zakat management institutions are among the main causes of suboptimal zakat collection. This study aims to analyze in more depth how levels of trust and zakat literacy influence the intention of payers to distribute zakat through Zakat Management Organizations (OPZ), considering the role of attitude as a mediating variable. Furthermore, this study seeks to provide empirical understanding of the relationship between psychological factors and religious behavior in the context of zakat compliance. This study used a quantitative approach through a survey of 400 muzakki respondents in Malang Raya, and the data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.4. The results showed that zakat trust and literacy significantly influenced muzakki attitudes, and attitudes were proven to mediate the relationship with muzakki intentions. These findings emphasize the important role of zakat institutions in building public trust and increasing literacy so that zakat management is more optimal and has a broad impact on community welfare.